PASANG SURUT KEKUASAAN PRESIDEN REPUBLIK INDONESIA BERDASARKAN UUD 1945 SEBELUM DAN SESUDAH AMANDEMEN - ISMAIL, M. (Universitas Mahasaraswati Mataram, 2018)
On August 18, 1945, for the first time the President and Vice President were elected by PPKI. In the early days of the administration, the power of the President in running the government was not only based on Articles 4.5,10,11,12,13,14 and 15 of the 1945 Constitution, but also based on Article IV of the Transitional Rules which read